Writing and rewriting the story of Solomon in the ancient Israel - Kalimi, Isaac (Cambridge : Cambridge University Press, 2019)
Solomon's image as a wise king and the founder of Jerusalem Temple has become a fixture of Jewish, Christian, and Islamic literature. Yet, there are essential differences between the portraits of Solomon that are presented in the Hebrew Bible. In this volume, Isaac Kalimi explores these differences, which reflect divergent historical contexts, theological and didactic concepts, stylistic and literary techniques, and compositional methods among the biblical historians. He highlights the uniqueness of each portrayal of Solomon - his character, birth, early life, ascension, and temple-building - through a close comparison of the early and late biblical historiographies. Whereas the authors of Samuel-Kings stay closely to their sources and offer an apology for Solomon's kingship, including its more questionable aspects, the Chronicler freely rewrites his sources in order to present the life of Solomon as he wished it to be. The volume will serve scholars and students seeking to understand biblical texts within their ancient Near Eastern contexts.
Title from publisher's bibliographic system (viewed on 11 Dec 2018).
Keywords: Solomon, -- King of Israel